Mindful learning : 101 proven strategies for student and teacher success - Campbell, Linda, 1948- 4 0 16; 1945- Campbell, Bruce; 5 (Thousand Oaks, CA : Corwin Press, 2009)
Presents over one hundred research and instructional strategies that have proven to be successful in the classroom, designed to meet the needs of students with diverse aptitudes and interests.
Includes bibliographical references and index.
Professional.
Keywords: 2 -- 0; 6; Effective teaching;Cognitive styles in children;Individual differences in children;Learning strategies;Teaching;Cognitive styles in children.;Child psychology.;Psychology of learning. -- United States.;United States.;United States.;United States.;United States; 20; 2